THERMAL LENSING MEASUREMENTS IN THE FLASHLAMP-PUMPED ANISOTROPIC LASER CRYSTALS BY A PROBE BEAM TECHNIQUE - P. A. Loiko; K. V. Yumashev; N. V. Kuleshov; A. A. Pavlyuk (Приборы и методы измерений, 2015)
The experimental setup for thermal lens properties determination (particularly, its sign, optical power, laser rod sensitivity factors and astigmatism degree) in the anisotropic flashlamp-pumped laser crystals by a probe beam technique was developed. By means of this approach, thermal lensing measurements were performed in the Np -cut Nd-doped potassium gadolinium tungstate (Nd:KGdW) laser crystal at the wavelength of 1,06 μm for light polarizations E || Nm и E || Ng. a